Minimizing Guidewire Unwilling Passage and Related Perforation During Transradial Procedures: Prevention Is Better Than Cure - Xu, Lili; Cao, Jiatian; Zhang, Meng; Yang, Hongbo; Huang, Zheyong; Song, Yanan; Li, Chenguang; Dai, Yuxiang; Yao, Kang; Wang, Xiangfei; Zhang, Feng; Qian, Juying; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Current guidewires for transradial coronary angiography had defects of passage difficulty or branch injury. This study sought to investigate the safety and efficiency of a novel method of active knuckle-angle 0.035-inch hydrophilic guidewire in transradial coronary angiography. Methods: Patients undergoing a transradial coronary procedure in our team from August 2015 to June 2020 were retrospectively investigated. We compared the demographic and interventional characteristics of 1457 patients receiving advancement of unmodified guidewires (Traditional group) and 1322 patients receiving advancement of the knuckle guidewire (Knuckle group). Afterwards we included 239 patients and randomized them according to a random number table to either the unmodified or the knuckle guidewire to further confirm the efficiency and safety of knuckle guidewire advancement. Results: In the retrospective analysis, unwilling passage of guidewire into branches occurred more in the Traditional group than in the Knuckle group (9.5% vs. 0.08%, p<0.001). 2 patients in the Traditional group experienced guidewire-associated perforation. One patient was treated with covered stent for internal mammarian artery perforation, while the other was managed with compression for brachial branch perforation. In the randomized controlled study, unwilling passage of guidewire also occurred more in the Traditional group (10.8% vs. 1%, p<0.001). Median duration of guidewire advancement from the sheath to aortic root significantly decreased from 33 seconds in the Traditional group to 21 seconds in the Knuckle group. Conclusions: Active knuckle angle guidewire represented a novel method to prevent unwilling passage and associated perforation with efficiency improvement and a reduction in radiation exposure.